Via negativa - Hornsby, Daniel (Alfred A. Knopf, 2020)
"A heartfelt, daring, and divinely hilarious debut novel about an old priest looking back on his life and grappling with his mistakes as he hits the highways of the American midwest with a pistol in his pocket and an injured coyote in his backseat. Father Dan is homeless. Dismissed by the church for eccentricity and insubordination, he's tried to transform his exile into a kind of pilgrimage, to make his Toyota Camry into a mobile monk's cell. But even this master of self-denial--and straight-up denial--knows when he's lying to himself: "I am a retired priest living out of his car. I am a retired priest, kicked out of his rectory and living in his car with a coyote and a bucket he shits in." Ahh, yes: the coyote. Alert to signs and wonders, Dan is swift to stop when he sees a wild coyote get hit by a minivan. The injured animal becomes Dan's unexpected traveling companion as he wends his way west through the heartland of America, nursing the coyote back to health and stopping to take in the occasional roadside attraction (MARTIN'S HOLE TO HELL, WORLD FAMOUS BOTTOMLESS PIT NEXT EXIT!). The farther he travels and the more people he meets, the more he is forced to reckon with a lifetime of regrets: the friendships he let dissolve, his gradual alienation from the church, and his fierce hatred of a particular predatory priest. Father Dan's true quest gradually starts to take shape. But is penance better paid with a journey of redemption . . . or revenge?"--